A Review of Qualitative and Quantitative phytochemical analysis for plant extracts. - GUPTA, DIVYANSHI; SINGH DANGI, CHANDRA BAHADUR; SIDDIQUI, SHADMA; SINGH, BAL BAHADUR (International Journal of Multidisciplinary Research and Studies, 2023)
Plants and their derivatives constitute a significant component of the human diet. They serve as a primary reservoir of biologically active compounds such as vitamins, dietary fiber, antioxidants, and cholesterol-lowering agents. Despite the abundance of information in this domain, the nutritional profile of plants remains inadequately characterized. Historically, identifying many plant nutrients and health-promoting substances relied on a trial-and-error approach. As the 21st century unfolded, advanced analytical techniques, including chromatography, mass spectrometry, infrared spectrometry, and nuclear magnetic resonance, revolutionized the field by enabling quantitative and qualitative assessments of a myriad of plant metabolites. The application of these methodologies has unveiled approximately 50,000 metabolites in plants, with projections anticipating the eventual discovery of over 200,000. Despite this wealth of information, the functions of a substantial proportion of these metabolites remain unknown. Crucial for plant growth, development, stress adaptation, and defense, metabolites such as carbohydrates, organic and amino acids, inorganic elements, vitamins, hormones, flavonoids, phenolics, and glucosinolates play pivotal roles. Beyond their significance for plant biology, these metabolites profoundly influence the nutritional quality of food, impacting aspects such as color, taste, and smell, and conferring antioxidative, anticarcinogenic, antihypertensive, anti-inflammatory, antimicrobial, and cholesterol-lowering properties. This review concentrates on elucidating major plant metabolites and detailing the methodologies employed in their analysis.